Nordic strategy for the Arctic climate and environmental pollutants : 2nd edition 2008 (Copenhagen : Nordic Council of Ministers, 2009)
The Arctic region is experiencing some of the fastest and severest climate change on Earth, with massive physical, ecological, social and economic changes that will have repercussions far beyond the Arctic. The Arctic also functions as the "destination" of long-range environmental pollutants transported by air or sea currents from more southern latitudes. Knowledge about climate change and documentation of environmental pollutants in the Arctic are of strategic significance to the Nordic Council of Ministers' and the Nordic countries' efforts to limit emission of greenhouse gases and reduce the supply of environmentally harmful substances. Adopted by the Nordic environmental ministers, this Nordic strategy for climate and environmental pollutants in the Arctic primarily aims to serve as a joint platform for continued internal environmental cooperation in the Nordic Council of Ministers and for cooperation between the Nordic countries in the areas covered by the strategy. The strategy covers the period from 2006 to 2012.